FLASH LiDAR SINGLE PHOTON IMAGING OVER 50 KM - Z. Q. Xia (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2023)
In order to demonstrate the feasibility of single-photon imaging of flash lidar in the permanent shadow area of the moon, a set of space-based single-photon imaging system is designed, including the lidar based on VCSEL array, the optical emitting system based on the uniform beam shaping meta-lens using propagation phase and geometric phase joint control method, the two-axis three-mirror optical receiving system, and the single-photon detector array based on photon counting mode. According to the heavy-tailed pulse laser function, Poisson statistical filtering theory and Monte Carlo simulation method, the echo photon number, the photon counting process, the ranging accuracy and the intensity image are simulated in the condition of 50 km detection distance by setting different of the object reflectivity, the repetition times and the gating interval time. The results show that according to the parameter settings in this paper, the number of echo photons is as low as about 10-4 orders. However, the photon counting waveform can better restore the transmission waveform. The setting of the repetition number and the gating interval time should not only consider the missing detection phenomenon, but also consider the noise accumulation. When the repetition number is 2000 and the gate number is 200, the ranging accuracy can reach 0.075m, and the imaging in the crater without light is realized.